distribusi spesial populasi simping (Placuna placenta) di Pesisir Tanggerang - Yonvitner Yonvitner; S Sukimin; K Praptokardiyo; I Setyobudiandi; R Dahuri (Jurnal Ilmu Pertanian Indonesia, 2007)
Simping population (Placuna placenta) represent a type of benthic biota and it immobility. This species disperse in any coastal and territorial water of Indonesia such as in north Banten coast, Bekasi coast, Tuban, Gresik and Kalimantan. Dispesion of simping in Banten coastal having differences with other site.